Gross Motor Coordination: We Have a Problem! A Study With the Körperkoordinations Test für Kinder in Youth (6-13 Years) - Matteo Giuriato; Matteo Giuriato; Valentina Biino; Valentina Biino; Marianna Bellafiore; Giuseppe Battaglia; Antonio Palma; Carlo Baldari; Laura Guidetti; Maria Chiara Gallotta; Federico Schena; Massimo Lanza (Frontiers Media S.A., 2021)
The main goal of our cross-sectional research was to determine the current values of gross motor coordination (GMC) of Italian boys and girls between 6 and 13 years of age. Secondary goals were to study gender differences, and the four subtests trend with ages. Results were compared with the references proposed by KTK authors and with similar searches. Anthropometric measurements and KTK data from 2,206 schoolchildren (girls: n = 1,050; boys: n = 1,156) were collected. The KTK raw score (RS) increased with the age of the subjects (r = 0.678; p < 0.001). In 11-13-year-old subjects, the increase in results is less than in younger subjects. RS showed differences by gender (F = 5.899; p = 0.015) and age (F = 269.193; p < 0.001) without interaction gender × age. Motor quotient (MQ) tended to decrease with age (r = −0.148; p < 0.001); it showed differences by gender (F = 79.228; p < 0.001), age (F = 14.217; p < 0.001), and an interaction gender × age (F = 2.249; p < 0.05). Boys showed better performance than did girls in the raw scores of three of four subtests (JS: F = 24.529; MS: F = 9.052; HH: F = 11.105). Girls show better performances than did boys in the WB (F = 14.52). Differences between genders make us believe it appropriate to maintain a differentiated standardization. RS increased with age, and it seems reasonable, therefore, to maintain a GMC age-based normalization. On the contrary, MQ tended to decrease. All this makes us speculate that today's young people accumulate less significant motor experiences over the years compared to those achieved by their peers in the 1970s. Italian data were lower than German references and Belgian results but slightly higher than the Brazilian ones. The comparison among these four searches confirmed a worrying downward trend in GMC and its characterization by geographical and sociocultural areas. Updated parameters of the KTK can provide helpful references to improve policies to support physical activity, sport, and physical education in youth.